The influence of forming path parameters on magnesium alloy multipass single‑point incremental forming with hot vibratory assistance - Su, Chunjian (2024)
In the study of multipass incremental forming, the influence of the interaction between thermal vibration and forming path parameters on the formed parts is often studied separately. However, this approach often fails to effectively control the forming quality, and comprehensive research combining both factors is scarce. Therefore, this paper focuses on a conical magnesium alloy workpiece with a 75° forming angle and investigates the influence of forming path parameters under the interaction of thermal vibration on the forming performance of magnesium alloy. First, a finite element model is established. Subsequently, through orthogonal experiments, the optimal combination of thermal vibration parameters is determined, and the influence of different forming paths on the stress, strain, wall thickness, and forming accuracy of the workpiece is analyzed. Finally, an optimization analysis is conducted on the forming path trajectory, followed by a computer numerical control experiment to verify the accuracy of the simulation results. The results show that the optimal combination of thermal vibration parameters is a forming temperature of 250 °C, an amplitude of 0.01 mm, and a vibration frequency of 30 kHz, increasing the minimum wall thickness of the workpiece by 6.32%. Moreover, gradually increasing the opening diameter of the workpiece can improve the side wall thickness but results in a larger bottom error. However, gradually increasing the forming depth of the workpiece reduces the bottom error but causes the side wall to thin. Path schemes based on axial compensation and tool trajectory adjustments can optimize bottom defects. By selecting appropriate forming parameters, the forming quality and efficiency were improved.